Development of “green” and organic production in dairy cattle breeding - L. A. Ovsyanko; N. I. Pyzhikova; M. A. Fedorova (Вестник университета)
The problem of creating environmentally friendly products has become particularly relevant during the COVID-19 pandemic from the standpoint of ensuring the health of the nation as well as from the point of view of increasing the competitiveness and efficiency of agricultural enterprises. Special attention should be paid to the issues of regulation and justification of the principles of building “green” and organic production that currently remain unsolved. The purpose of this study is to justify the priority of technological development in the agricultural sector of the economy by comparing development trends in the global and domestic market of organic products considering the analysis of the formation of the legislative framework in this area of activity as well as identifying industry principles of the typical for dairy cattle breeding production. The methods of analysis, synthesis, comparison, and generalization were used in the article. The results of the study can serve as a basis for the sustainable development of “green” and organic production, both in dairy cattle breeding and other sectors of agriculture as well as basis for the development of federal and regional programs for the organic market growth in the Russian Federation.